2014
DOI: 10.12998/wjcc.v2.i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde jejunogastric intussusception following Braun’s jejunojejunostomy

Abstract: Jejunogastric intussusception is a rare long term complication of Billroth II gastrectomy. The case reported here is a 50 year old man with history of a Billroth II gastrectomy and Braun's side-to-side jejunojejunal anastomosis who presented with hematemesis. On abdominal examination, there was a mass in the left iliac fossa. Computed tomography scan showed a retrograde jejunogastric intussusception across the gastrojejunostomy. On laparotomy, a retrograde intussusception of the distal jejunum through the jeju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Our patient had an exacerbation of the symptoms characterized by the appearance of vomiting and an alteration of transaminases and amylases, according to the Literature but without specific symptoms of intussusception. All Authors agree with the importance of the CT-scan as the gold standard for the diagnosis with an accuracy of 80% [4,5,14,17,26]. CT specific signs are: "target" imagine which confirms the presence of bowel wall intussuscepted inside the tract that appears expanded the "telescope" sign when the intussuscepted bowel seems a telescope into the adjacent distal intestinal loop (Figure 3 & 6) [27][28].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our patient had an exacerbation of the symptoms characterized by the appearance of vomiting and an alteration of transaminases and amylases, according to the Literature but without specific symptoms of intussusception. All Authors agree with the importance of the CT-scan as the gold standard for the diagnosis with an accuracy of 80% [4,5,14,17,26]. CT specific signs are: "target" imagine which confirms the presence of bowel wall intussuscepted inside the tract that appears expanded the "telescope" sign when the intussuscepted bowel seems a telescope into the adjacent distal intestinal loop (Figure 3 & 6) [27][28].…”
Section: Discussionmentioning
confidence: 74%
“…Intussusception after near total gastrectomy is a rare cause of intussusception, with an increasing incidence [2,3]. It is usually associated with lesions defined "lead point", such as cancer, polyps, adhesion it is defined anterograde or retrograde by isoperistaltic or antiperistaltic behavior of the intestinal loop intussuscepted [4][5][6][7][8][9][10][11][12][13][14]. Its pathophysiology after near total gastrectomy is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, endoscopic reduction of JGI has a risk of recurrence and surgery remains the treatment of choice [4,7,9]. Emergency surgical intervention is necessary in most cases and can prevent clinical deterioration [10]. Surgery for JGI can be simple reduction or resection and refashioning of the gastroenterostomy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Literature review showed that just over 200 cases have been reported, most of them being case reports and small series. [2][3][4][5] The reported incidence is less than 0.1% to 0.15%. 7,8 Retrograde intussusception was also reported in patients after Billroth-I reconstruction, Billroth-II reconstruction, previously placed gastrostomy tubes, pancreaticojejunostomy and total gastrectomy with Roux-en-y-anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors describe Type IV, which consists of over intussusception through a braun side-to-side jejunojejunal anastomosis. 3,5 The etiopathogenesis and mechanism of JGI are unclear and poorly understood. The major theories suggested are functional and mechanical.…”
Section: -49-11mentioning
confidence: 99%